Paradise on fire - Rhodes, Jewell Parker (Little, Brown and Company, 2021)
Addy's parents were killed in a tragic fire years ago, and she still carries the trauma of this loss with her wherever she goes. When her grandmother sends her to a summer wilderness program in California, Addy finds herself learning to live in the forest with five other Black city kids. But those survival skills are soon put to the test when a forest fire erupts in the woods where they are camping.